The Effect of Providing 10t Antenatal Care Services on Pregnant Women's Visits At UPTD Popayato Health Center - Desriyanti Nusi; Anik Sri Purwanti; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Antenatal Care (ANC) is one of the important aspects in maintaining the health of pregnant women and fetuses. Provision of good and standard antenatal care services, one of which is the 10T program, plays an important role in reducing maternal and infant mortality rates. However, visits by pregnant women to health centers often do not match the expected number. Therefore, this study aims to determine the effect of providing 10T ANC services on the level of visits by pregnant women at the Popayato Health Center UPTD. This study aims to determine the effect of providing 10T antenatal care services on the level of visits by pregnant women at the Popayato Health Center UPTD. This type of research is quantitative with a pre-experimental design using a one group pretest-posttest approach. The study was conducted at the Popayato Health Center UPTD involving 16 pregnant women respondents who were registered during the study period. Data were obtained through observation and interviews, and tested using the Wilcoxon test. The results of the Wilcoxon test obtained a p value = 0.000, which means p-value <0.05. This shows that there is a significant influence between the provision of 10T ANC services on increasing visits by pregnant women at the Popayato Health Center UPTD. Before the intervention, the majority of pregnant women did not make regular visits, but after being given 10T ANC services, almost all respondents increased the frequency of their visits. The provision of 10T antenatal care services has a significant effect on increasing the level of visits by pregnant women at the Popayato Health Center UPTD. The implementation of the 10T program can increase the awareness of pregnant women to undergo regular visits, which has a positive impact on the health of the mother and fetus. For health workers, it is hoped that they will continue to improve the quality of 10T ANC services in order to attract more pregnant women to make regular visits. It is hoped that health facilities will educate pregnant women more often about the importance of 10T ANC services. Further research with a larger sample size can be conducted to strengthen these findings